KOSAKATA BUDAYA TRADISI PENANGKAPAN KOTEKLEMA DI LAMALERA DALAM NOVEL “SUARA SAMUDRA, CATATAN DARI LAMALERA” SEBAGAI SALAH SATU ALTERNATIF PENGAYAAN KOSAKATA BAHASA INDONESIA - Nining Nur Alaini (Balai Bahasa Nusa Tenggara Barat, 2018)
The three local languages mentioned in the National Language Policy formulated in the Language Politics seminar organized by the Language Center (now the Agency for Language Development and Development) in 1999 function as a language symbols including a symbol of regional identity, and a symbol of regional pride; a mean of communication in the family and local communities, and a mean of supporting regional culture and as a supporter of regional literature and Indonesian literature. As a means of supporting the Indonesian language, regional languages have a dominant role in enriching the Indonesian vocabulary. This paper will describe the cultural vocabulary in the tradition of capturing the koteklema in Lamalera in the novel of